Impact of trophoectoderm biopsy for preimplantation genetic testing on serum β-hCG levels, time of delivery and birthweight following frozen embryo transfer cycles - Özkan Özdamar; F. Kübra Boynukalin; Meral Gültomruk; Zalihe Yarkiner; Necati Findikli; Mustafa Bahceci (Taylor & Francis Group, 2023)
Aim: This study investigated whether trophoectoderm (TE) biopsy adversely impacts serum β-human chorionic gonadotropin (hCG) level on the 15th day of embryo transfer (ET), delivery week and birthweight, between biopsied and unbiopsied embryo groups, in a cohort of women who delivered a singleton baby, following frozen-thawed ET.Methods: All women having had a live birth after blastocyst ETs following frozen ET cycles with preimplantation genetic testing (PGT) were included. A control group was selected among women who had a live birth following single frozen blastocyst transfer without PGT-A at the same period in our clinicResults: One hundred fifteen and 173 cycles with- and without-PGT, respectively, were included. Serum β-hCG level on the 15th day after ET was comparable between the groups (p = .336). Average birthweight of the babies born following biopsied embryos were significantly lower (3200 vs. 3380; p = .027). Women who received trophectoderm biopsied embryos had a significantly higher probability of having a baby weighing ≤1500 g and 1500-2500 g (p = .022) or ≤2500 g (p = .008). Proportion of preterm delivery was significantly higher in the biopsy group (p = .023). However, after adjusting for potential covariates, trophectoderm biopsy did not seem to increase the risk of preterm birth (OR 1.525; 95% CI, 0,644-3.611; p = .338)Conclusions: TE biopsy does not seem to impact serum β-hCG level on the 15th day after ET. Average birthweight is lower when a biopsied embryo was transferred. After adjusting for potential covariates, trophectoderm biopsy does not seem to increase the risk of preterm birth